Birds of Behali Wildlife Sanctuary, an Important Bird Area of Assam, India - Kakati, Ranjit; Borah, Dipankar; Saikia , P.K.; Hazarika, Ajit (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2022)
The avian diversity of Behali Wildlife Sanctuary, an Important Bird Area IN-AS-05 (A1 and A3) is documented here. A total of 283 species of birds belonging to 21 orders, 69 families, and 194 genera were recorded. The study recorded one critically endangered species, 2 endangered species, 7 vulnerable species, 13 near threatened species and 260 species were least concern. Distribution of birds within the reserve forest and IUCN Red List Categories of them are also provided here.